Photobiomodulation after Surgical Extraction of the Lower Third Molars: A Narrative Review - Daniele Pergolini; Alessandro Del Vecchio; Gaspare Palaia; Federica Rocchetti; Raffaele Cefalà; Riccardo De Angelis; Gianluca Tenore; Umberto Romeo (MDPI AG, 2022)
The surgical extraction of the lower third molar is widely practiced in oral surgery. Inflammatory complications such as pain, swelling, and trismus can cause discomfort to the patients after third molar extraction. Several methods have been used to reduce these postoperative sequelae, including the use of corticosteroids, nonsteroidal anti-inflammatory drugs, analgesics, antibiotics, less traumatic surgical methods, and the use of photobiomodulation. This narrative review summarizes the current evidence on the effect of photobiomodulation on pain, facial swelling and trismus after third molar surgery. A literature search using MEDLINE (NCBI PubMed and PMC), EMBASE, Scopus, Cochrane library, Web of Science, and Google Scholar was undertaken up to October 2021. Forty-one articles met the inclusion criteria. Photobiomodulation can be considered an alternative and useful method for controlling pain following impacted wisdom tooth surgery. The effectiveness of PBM in reducing swelling and trismus is still controversial. This review highlights the lack of consensus in the literature on protocols used in PBM therapy.